INSTITUTIONAL PROVISION OF GEOLOGICAL STUDY AND USE OF SUBSOIL: NATIONAL AND INTERNATIONAL EXPLORATION - Balega А.; Vyzhva, S.; Kurylo М. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The national experience of institutional support for the study and use of subsoil are defined. The subjects of interaction in the sphere of geological mining use are defined, the mechanism of interaction is shown. The institutional provision of the study and use of subsoil is divided into three blocks of influence: institutions of general competence, inter-sectoral institutions of special competence and sectoral institutions of special competence. The role of the State Service of Geology and Mineral Resources of Ukraine in the system of institutional support of geological study and use of subsoil is determined. The structure of the State Service of Geology and Mineral Resources of Ukraine was systematized and the basic functions and directions of activity are defined. It is revealed that state financing of development of mineral base of Ukraine takes place through the system of enterprises and organizations belonging to the State Service of Geology and Mineral Resources of Ukraine. The structure and features of geological services in Germany, Poland and Australia were investigated. In the course of this analysis, a number of typical and a number of distinctive functions were identified for the geological services of the above mentioned countries. The State Service of Geology and Mineral Resources of Ukraine does not provide a number of key and progressive functions in the field of geological study and use of subsoil, such as: monitoring the state of the market of mineral resources, popularization of the mineral raw materials complex and enhancement of the investment attractiveness of the mineral base of Ukraine. It is concluded that for the introduction of foreign experience, changes should be made to the structure of the State Service of Geology and Mineral Resources of Ukraine. The study of the functional experience and the role of geological services in Australia and Germany testify to the effectiveness of regional geological services in the development of mineral base of these countries. Since the decentralization process in Ukraine has not been completed, experience in providing broad powers to local government bodies, a mineral base cannot be easy implemented.